Right Ventricular Longitudinal Function in the Assessment of Fluid Responsiveness in Healthy Dogs - Buba Lucina, Stephany; Muehlbauer, Eloisa; Bentivóglio Costa Silva, Vinícius; Folgearini Silveira, Matheus; Wolf, Marcela; Pereira dos Santos, Julio; Carlos Duque Moreno, Juan; Gonçalves Sousa , Marlos; Rodrigues Froes, Tilde (Acta Scientiae Veterinariae, 2024)
Background: An essential component in the treatment of critically ill patients is volume replacement, but excessive intravascular fluid administration is associated with increased morbidity and mortality. Therefore, this intervention is only beneficial in patients who are fluid responsive, that is, when the individual has an increase in at least 15% of the stroke volume after a volume challenge administration. In addition, one of the determinants of fluid responsiveness is the systolic function, associated with the dynamic interactions between intravascular volume (preload) and vascular tone (afterload). Within this context, the aim of this study is to evaluate if conventional and advanced echocardiographic parameters of right ventricular longitudinal systolic function can assess fluid responsiveness in healthy spontaneously breathing dogs. The hypothesis was that some of these parameters would differ between responsive and non-responsive animals and could be used as a complementary measure for assessment of fluid responsiveness. Materials, Methods & Results: This is a prospective study with 22 healthy dogs over 1 year of age included. The animals were referred to the Veterinary Medical Teaching Hospital of the Federal University of Paraná (UFPR) for elective neutering procedure. All dogs underwent conventional and advanced echocardiographic examination before and after administration of a volume challenge with 10 mL/kg lactate ringer intravenously for 20 min. The parameters evaluated were the fractional area change (FAC), the tricuspid annular plane systolic excursion (TAPSE), free wall longitudinal strain (LSt), and tissue motion annular displacement (TMAD). Based on the aortic velocity integral time variation, 31.82% of dogs were considered responsive and 68.18% were non-responsive to the volume challenge. For conventional echocardiography, TAPSE (mm/kg) > 1.35 (P = 0.018) had a good combination of sensitivity (85.71%) and specificity (86.67%), area under the curve value (0.814) and a relative smaller gray zone interval (1.04-1.66) for the identification of responsive dogs before volume challenge. Although, TAPSE (mm/m2) was also higher in the responsive dogs (P = 0.023) before volume challenge. As for advanced echocardiography, the TMAD (mm/kg) > 0.75 (P = 0.010) after volume challenge had the best combination of sensitivity (85.71%) and specificity (86.67%), area under the curve value (0.852) and a relative smaller gray zone interval (0.57-0.92) for the identification of responsive dogs. The LSt (%) and TMAD (mm/m2) were also significantly higher in responsive dogs (P = 0.031; P = 0.011) after volume challenge. Discussion: Some of the echocardiographic parameters for assessing right ventricular systolic function differed between responsive and non-responsive dogs proving to been useful in the fluid responsiveness evaluation. To the author’s knowledge, this is the 1st study to investigate the right ventricular systolic function in the assessment of fluid responsiveness in healthy, spontaneously breathing dogs. TAPSE and TMAD showed some advantages in terms of execution, although TAPSE (mm/kg) > 1.35 before the volume challenge had the power to predict fluid responsiveness without the need of a fluid administration, which can be seen as a great advantage, especially for patients with volume overload. However, it is also necessary to perform this type of evaluation in individuals with hemodynamic alterations to allow better understand the applicability of these techniques. Keywords: canine, longitudinal strain, stroke volume, tissue motion annular displacement.